An investigation into the vaccine responsiveness of multiple sclerosis patients being treated with Ocrelizumab - Thomas, Niamh (2024)
Multiple Sclerosis (MS) is a chronic inflammatory demyelinating disease of the central nervous system (CNS), and the most common non-traumatic disabling disease affecting young adults. The exact etiopathogenesis remains elusive however major advances in the understanding of the disease have been made in the last few decades. The traditional view of T cells being the main players in the pathophysiology of MS has evolved and focus has shifted to the complex role of B cells and their contribution to disease progression, which is highlighted by the success of B-cell depleting therapies. Ocrelizumab is a humanised anti-CD20 monoclonal antibody approved by the FDA in 2017 for the treatment of people with Relapsing Remitting MS (RRMS) and Primary Progressive MS (PPMS). With the use of ocrelizumab, over 99% of peripheral B cells in the blood are depleted, which can last anywhere between 24 and up to 175 weeks. This study aimed to examine the impact of ocrelizumab on both the quantity and quality of antibodies produced in response to vaccinations as well as its broader influence on immunological memory. Finger prick blood samples were collected from people with MS, providing precise volume of blood from which antibodies could be measured and analysed. Short-term vaccine responses were assessed using ELISAs, measuring antibody reactions to SARS-CoV-2 proteins (Spike, RBD, Nucleocapsid). To explore longer-term immune memory, a microarray platform was developed to examine responses to various antigens. We designed a microarray antigen platform, containing viral-recall antigens and pathogen associated antigens in order to assess hundreds of MS patient IgG responses in a high-throughput manner. The study revealed that ocrelizumab treatment had a significant impact on both humoral responses to recent vaccines and longer-term recall responses. Notably, despite being vaccinated, many ocrelizumab-treated people with MS exhibited inadequate antibody responses to SARS-CoV-2 vaccinations compared to untreated people with MS. Additionally, patients overall demonstrated diminished responses to recall antigens. These findings underscore the importance of continued research into ocrelizumab and its implications for the immune system. Understanding its effects on vaccine responses and immunological memory will aid in optimizing treatment strategies for people with MS and enhance our knowledge of B-cell involvement in the pathophysiology of this complex disease.